African Competitiveness and the Business Environment: Does Manufacturing Still Have a Role to Play?. (7th September 2022) - Aryeetey, Ernest; Baffour, Priscilla Twumasi
Abstract: Although most African economies have grown and only partially diversified over the past decades, growth in manufacturing output has, at best, stalled. This poor performance of manufacturing in Africa has led to scepticism about the future of manufacturing-led transformation in the region in recent times. This notwithstanding, we argue in this paper that manufacturing-led industrialisation is still possible in Africa and can be achieved by increasing the global competitiveness of manufacturing in the region. Particularly, with a youthful population and a growing labour force in an ageing world, opportunities exist for manufacturing development. Consequently, the paper investigates drivers of manufacturing competitiveness in Africa using the system-generalized methods of moments technique with annual data over the period 2003–2018 for 41 African countries. The findings of the paper are as follows: infrastructure and good governance positively influence manufacturing competitiveness in Africa, exchange rate depreciation stimulates manufacturing competitiveness, the size of domestic market and agglomeration of firms have important positive effects on manufacturing competitiveness and, finally, there is the existence of a U-shaped relationship between manufacturing competitiveness and GDP per capita in Africa. The findings of the paper point to the need for African governments to take a critical look at infrastructure development as a precondition to developing the manufacturing base to make the sector globally competitive in addition to improvement in the regulatory environment through good governance and strong institutions while maintaining good exchange rate policies to avoid currency overvaluation. The paper concludes with the observation that recent increases in income in the region will not generate industrialisation as earlier hypothesised, unless African governments intentionally identify and address the challenges working against manufacturing competitiveness on the continent.